Efektifitas Audit Internal Syariah di Perbankan Syariah - Nurul Fatimah; Muhammad Hamdan Ainulyaqin (Jurnal Indonesia Sosial Teknologi, 2022)
The main objective of this study is to determine the most effective factors that can play an important role in increasing the effectiveness of Islamic internal audit in the Islamic banking industry. This research is a qualitative method using scientific journal literature searches, and data collection was carried out using the Emerald online database. Sharia banking was established which has the aim of increasing economic activity in accordance with sharia principles, there is no usury, speculation, maysir, gharar and other activities that have been prohibited in sharia. Sharia internal audit is a way to maintain and ensure the integrity of Islamic financial institutions in implementing sharia principles. The existence of sharia internal audit for Islamic banking, provides assurance and independent accountability for stakeholders. the competence of the internal auditors is not enhanced, especially competencies related to the auditor's knowledge of muamalah sharia/fiqh or sharia audit which can be proven by holding a sharia-related certification. In carrying out their duties as an internal auditor, they must have competency qualifications to know and understand how the actual condition of sharia principles is so that they can identify if a violation occurs that is not in accordance with sharia principles both in transactions and operations.